2016
DOI: 10.1039/c6cy01025c
|View full text |Cite
|
Sign up to set email alerts
|

Gas phase oxidation of 2-methyl-1,3-propanediol to methacrylic acid over heteropolyacid catalysts

Abstract: Heteropolyacids with Cs, V and Cu partially oxidize 2MPDO to methacrylic acid (40% selectivity) in the gas phase at 250 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Gas-and liquid-phase oxidation of 2-methyl-1,3-propanediol (C 4 H 10 O 2 )t om ethacrylic acid( C 4 H 6 O 2 )a ccordingt oC 4 H 10 O 2 + 2O 2 !C 4 H 6 O 2 + 2H 2 Ow as shown [33] to occur over heteropoly- and Cu promoter, such as Cs x (NH 4 ) 3Àx PMo 12 O 40 (VO)Cu 0.5 ,w hich replace acetone cyanohydrin [(CH 3 ) 2 C(OH)CN] in the ACH process, which is known to provide large quantities of unwanted ammoniumb isulfate byproduct duet of acile decomposition to acetone and hydrogen cyanide, which is particularly toxic. This is an importanti mprovement, as methyl methacrylate can be polymerized to poly(methyl methacrylate), which is known as Plexiglasso r Altuglassa nd is used for coatings and paints.…”
Section: Recent Developments In Academia and Industry And Challenges mentioning
confidence: 84%
See 1 more Smart Citation
“…Gas-and liquid-phase oxidation of 2-methyl-1,3-propanediol (C 4 H 10 O 2 )t om ethacrylic acid( C 4 H 6 O 2 )a ccordingt oC 4 H 10 O 2 + 2O 2 !C 4 H 6 O 2 + 2H 2 Ow as shown [33] to occur over heteropoly- and Cu promoter, such as Cs x (NH 4 ) 3Àx PMo 12 O 40 (VO)Cu 0.5 ,w hich replace acetone cyanohydrin [(CH 3 ) 2 C(OH)CN] in the ACH process, which is known to provide large quantities of unwanted ammoniumb isulfate byproduct duet of acile decomposition to acetone and hydrogen cyanide, which is particularly toxic. This is an importanti mprovement, as methyl methacrylate can be polymerized to poly(methyl methacrylate), which is known as Plexiglasso r Altuglassa nd is used for coatings and paints.…”
Section: Recent Developments In Academia and Industry And Challenges mentioning
confidence: 84%
“…Gas-and liquid-phase oxidation of 2-methyl-1,3-propanediol (C 4 H 10 O 2 )t om ethacrylic acid ( C 4 [33] to occur over heteropoly-…”
Section: Recent Developments In Academia and Industry And Challenges mentioning
confidence: 99%
“…Microfluidized bed reactors have distinct advantages compared to fixed bed reactors to measure kinetics and develop processes relying on vaporizing liquids. , Heat transfer rates are an order of magnitude higher, which ensures the reactor operates isothermally, minimizes hot spots, but more importantly heats the aerosol from the sparger rapidly. Furthermore, solids mixing minimizes radial concentration gradients.…”
Section: Resultsmentioning
confidence: 99%
“…Fluidized bed reactors are more appropriate than fixed bed reactors due to higher heat and mass transfer rates and shorter contact times (<1 s). Dalil et al reported the dehydration of glycerol to acrolein, while Keggin type catalyst oxidized 2-methyl-1,3-propanediol to methacrylic acid, spraying the reactants directly in the catalytic bed. , As a first catalyst, we chose WO 3 /TiO 2 because of its efficacy to dehydrate glycerol to acrolein operating under similar conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation